Late-Stage Alkylation of N-Containing Heteroarenes Enabled by Homolysis of Alkyl-1,4-dihydropyridines under Blue LED Irradiation - Chen, Xiaoping; Luo, Xiaosheng; Wang, Kaiqian; Liang, Feng; Wang, Ping (Synlett, 2020)
Alkylated heteroarenes are widely found in bioactive molecules and pharmaceuticals. Therefore, there is great interest in developing a chemoselective alkylation of heteroarenes under mild conditions, particularly during a late-stage functionalization step for the purpose of rapid derivatization. Herein, we introduce an efficient visible-light-promoted C–H alkylation of nitrogen-containing heteroarenes by using C4-alkyl 1,4-dihydropyridines (DHPs) as radical precursors at ambient temperatures. A broad scope of heteroarenes, such as 4-hydroxyquinazoline and its derivatives, including those bearing electron-donating or electron-withdrawing groups, can be successfully alkylated in good yields by using various C4-alkyl DHPs.
Keywords: alkylation; hetarenes; dihydropyridines; photochemistry; C–H functionalization